Automatic Canopy Drive System Against Weather Changes - Febriana, Erizarawati; Mukhaiyar, Riki (Journal of Industrial Automation and Electrical Engineering, 2024)
Unpredictable weather changes are a challenge in everyday life, especially in household activities such as drying clothes. This study develops an automatic canopy drive system based on the Internet of Things (IoT) to respond to weather changes in real-time. This system uses a NodeMCU ESP8266 microcontroller connected to the Blynk application and various sensors, including a rain sensor, light sensor (LDR), and temperature sensor (DHT11). These sensors detect environmental conditions and control the opening and closing of the canopy automatically to protect the drying area. Tests show that the system works optimally with temperature parameters of more than 25°C, light intensity of more than 10,000 lux, and no rain conditions to open the canopy, while if one of the conditions is not met, the canopy will automatically close. With a monitoring feature via a mobile application, this system provides convenience and efficiency for users in dealing with unpredictable weather changes.